The role of thoracic ultrasonography in the assessment of extravascular lung water and breathlessness - Corcoran, J (2019)
Patients with respiratory failure and breathlessness frequently present clinicians with a unique diagnostic and therapeutic challenge. These patients may be acutely unwell and in need of rapid intervention with limited information available to guide the responsible clinician. The range of different conditions that can present with breathlessness is broad, and differentiating one from another may be extremely difficult in a patient with multiple overlapping co-morbidities. Even when the cause of a patient’s breathlessness appears obvious, as can be the case with malignant pleural disease, identifying the best treatment option for that individual may not always be a straightforward process.